JURISTIC STUDY ON CONDITIONALITY OF AL-MAHRAM FOR NIGERIAN FEMALE HAJJ (PILGRIM): IMPLICATIONS AND SOLUTIONS - Muhammad JÄmiÊ»u, Elesin Ê»Abdulwahab (Jurnal Syariah, 2017)
The requirement for a female Muslim to have a mahram when traveling is not peculiar to hajj and 'umrah alone. However, in the contemporary period, the Kingdom of Saudi Arabia has become very strict on such a condition, especially on 'umrah and hajj. The legal implication of this system is that a female Muslim may not participate in hajj or 'umrah if her mahram cannot perform hajj or 'umrah with her for various reasons. However, this study reveals that the result of such a strict condition has led operators of the hajj and 'umrah to falsify data by applying for their visa through another male pilgrim who is not their legal mahram. Eventually, such intending female pilgrims end up performing the hajj or 'umrah with a group of trustworthy women or men, as has been rightly supported by a reasonable numbers of independent jurists. It is worthy of note that this practice of accompany with a mahram for a travelling female Muslim originates from the statement of the Messenger of Allah (SAW) due to the prevailing circumstances of the ummah at his time. The practice of his noble companions after him support this understanding. This paper analyzes the legal precedent and reasoning behind this condition and offers reasonable, practical and meaningful solutions.